(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify dissatisfaction with body image among university students in terms of gender and obesity. The research sample consisted of 400 male and female students was chosen randomly from the first and third stages at the University of Baghdad, including the scientific and humanities specialization for the academic year 2023-2024. To achieve the objective of the research, the researcher developed a scale of 42 items to measure dissatisfaction with body image according to psychological theoretical approaches analytical and psychosocial cognitive body image distributed over five domains: cognitive, behavioral, cognitive, emotional, and social domain. The results revealed that the research sample has dissatisfaction with body image. There are no significant differences among the research sample in dissatisfaction with body image in terms of gender. There are significant differences among the research sample in dissatisfaction with body image in terms of obesity, in favor of obese people. In light of the results of the research, the researcher came out with some recommendations and suggestions.